Effect of annealing treatment and infill percentage on 3D-printed PEEK samples by Fused Filament Fabrication - Lannunziata, Erika; Colucci, Giovanna; Minetola, Paolo; Giubilini, Alberto (International journal of advanced manufacturing technology, 2024)
A strategy that is gaining momentum in several industrial sectors is metal replacement, which aims to find suitable alternatives for replacing metal components with lighter ones. One possible solution is represented by high-performance polymers (HPP), which are a family of materials with improved thermo-mechanical and functional properties, compared to commodity plastics. Additive manufacturing (AM) is revolutionizing the industrial world due to its high design freedom, dimensional accuracy, and shortened total production time. Thus, combining the use of HPP with AM technologies could lead to innovative results, which could offer new metal replacement solutions through redesign and new material properties. However, HPPs have some manufacturing limitations, for example, they require high processing temperatures, and some of them are subject to significant warping and deformation phenomena. This aspect is particularly significant for semi-crystalline polymers, as in the case of poly(ether-ether-ketone) (PEEK), which is affected by thermal gradients during 3D printing. In this research, an investigation was carried out on the Fused Filament Fabrication (FFF) of different 3D printed PEEK samples, evaluating the effect on final properties not only of various infill percentages (30%, 50%, 70%, and 100%) but also of two different heating treatments. In this regard, a traditional annealing in oven, post 3D printing, was compared to a direct annealing approach, performed during FFF. The mechanical performance of the samples was characterized through tensile and compression tests along with the thermal properties and the thermal stability. In addition, for all different cases, energy consumption was measured, to provide an indication of the sustainability of the presented approaches. The findings suggest that the direct annealing solution holds promise and merits further investigation to bridge knowledge gaps in this domain. This research contributed to advance the understanding of PEEK 3D printing by FFF and played a vital role in the practical implementation of metal replacement as a sustainable strategy across various industrial applications.